2019
DOI: 10.1177/0958305x19882388
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of emission trading scheme on China’s thermal power industry: A pre-evaluation from the micro level

Abstract: Emission trading scheme is known as a cost-effective measure for mitigating CO2 emissions, and recently, China has started the world's largest carbon trading system. As the most influential industry in determining China's overall CO2 emission level, the thermal power industry will be greatly affected by nationwide carbon market in the near future. This paper explores the impact of the upcoming national emission trading scheme on China's thermal power industry at firm level. First, based on empirical data of 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Song et al (2015) and Tang et al (2020b) suggested that the pollution rights trading system, as a means of environmental governance, is designed to incentivize enterprises to achieve the goal of sustained reductions in pollution emissions and to improve Frontiers in Environmental Science frontiersin.org their production technology and total factor productivity through market-based means. Zeng et al (2020) constructed an empirical analysis framework at the microenterprise level based on empirical data from 478 thermal power plants and found that the pollution rights trading system has a positive impact on carbon dioxide emission reductions in Chinese power plants. Using data from Guangdong Province, Cheng et al (2016) found that the pollution rights trading system can significantly reduce nitrogen dioxide and nitrogen oxide emissions in Guangdong Province.…”
Section: Gains Of Local Governmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al (2015) and Tang et al (2020b) suggested that the pollution rights trading system, as a means of environmental governance, is designed to incentivize enterprises to achieve the goal of sustained reductions in pollution emissions and to improve Frontiers in Environmental Science frontiersin.org their production technology and total factor productivity through market-based means. Zeng et al (2020) constructed an empirical analysis framework at the microenterprise level based on empirical data from 478 thermal power plants and found that the pollution rights trading system has a positive impact on carbon dioxide emission reductions in Chinese power plants. Using data from Guangdong Province, Cheng et al (2016) found that the pollution rights trading system can significantly reduce nitrogen dioxide and nitrogen oxide emissions in Guangdong Province.…”
Section: Gains Of Local Governmentsmentioning
confidence: 99%
“…1) At present, some scholars have paid attention to the importance of promoting the synergy between the third-party treatment of environmental pollution and the pollution rights trading system but have focused mainly on the institutional basis and practical reasons for the participation of third-party pollution-control enterprises in pollution rights trading (Ren, 2023); moreover, no scholars have been able to explicitly propose specific ways in which to realize the synergy between the two. 2) Current studies on the third-party governance of environmental pollution (Zhou C. H. et al, 2019;Wu et al, 2023) and pollution rights trading systems (Zeng et al, 2020;Yao et al, 2022) are abundant, but in terms of the path of third-party pollution-control enterprises in participating in pollution rights trading, there are only a relatively small number of qualitative jurisprudential studies (Ren, 2023), and no scholars have yet quantitatively studied the reasonable path through which third-party pollution-control enterprises actually participate in pollution rights trading. 3) In terms of the definitions of responsibility for pollution-discharging enterprises and third-party pollution-control enterprises, existing scholars have noted that how to divide responsibilities (Tang et al, 2019;Zhou, 2023) and how to define these responsibilities remain unclear (Wu et al, 2023); additionally, scholars have proposed solutions such as the "polluter pays principle" (Zahar, 2019) and the "principle of sharing responsibility" (Huang et al, 2023), but these means have not completely solved the problem of defining third-party governance responsibilities for environmental pollution.…”
Section: Frontiers Inmentioning
confidence: 99%
“…Institutional investors, according to Jahanger, (2021a); Bolton and Kacperczyk, (2021); Yu and Wang, (2021); Yu and Liu, (2022), apply exclusionary screening in a few major industries based on the direct emission rate. Byrd & Cooperman, (2018) ;Zeng, et al, (2020), on the other hand, believe that if carbon emissions are not included in investing choices, investors and assets may be exposed to hazards. Zafar et al (2019) investigated the influence of the stock market, banking sector development, and renewable energy on carbon emissions in the G-7 and N-11 countries using the panelbootstrap-cointegration technique.…”
Section: Nexus Between the Stock Market And Co 2 Emissionsmentioning
confidence: 99%
“…Lu et al (2021) demonstrated that the carbon trading policy, which has led to additional costs, has less impact on the industrial competitiveness. Zeng et al (2020) also reported that the emissions trading scheme reduces CO 2 emissions from power plants and can reduce the total abatement costs from 0.37 to 41.5% in China. Tan et al ( 2019) using an optimization model found similar results for thermal power generation.…”
Section: Literature Reviewmentioning
confidence: 99%